2021
DOI: 10.1002/fft2.75
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota profiles and dynamics in fermented plant‐based products and preliminary assessment of their in vitro gut microbiota modulation

Abstract: Consumption of fermented food has long been associated with health benefits, but there is still limited knowledge on the bacterial dynamics in plant‐based food fermentation outside of culture‐based studies. Different fermented plant‐based products were assessed for the presence of Archaea and their microbiota bacterial dynamics during the fermentation. Archaea were consistently detected in the brine of the vegetables, and constant increase in gene copy number throughout the fermentation of kraut indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Lactobacillus and Bifidobacterium relative abundance was lower than the control but were two times and 10 times higher, respectively, than the sauerkraut samples. During the early stages of sauerkraut fermentation, Enterobacteriaceae levels in the food matrix have been shown to remain high ( Lavefve et al, 2021 ). Our study, concurrent with others, observed increasing LAB counts during fermentation, with a peak at around 13days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacillus and Bifidobacterium relative abundance was lower than the control but were two times and 10 times higher, respectively, than the sauerkraut samples. During the early stages of sauerkraut fermentation, Enterobacteriaceae levels in the food matrix have been shown to remain high ( Lavefve et al, 2021 ). Our study, concurrent with others, observed increasing LAB counts during fermentation, with a peak at around 13days.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies explore how being part of a whole fermented food matrix affects microbial viability during fermentation, storage, and gastrointestinal (GI) transit ( Buriti et al, 2010 ; Fiorda et al, 2016 ; Valero-Cases et al, 2017 ; Yang et al, 2020 ). Even fewer investigate the effect of whole fermented food consumption on the gut microbiota ( Lavefve et al, 2021 ). The human gut microbiota is an important dietary target, with its central regulatory role in immune function and energy metabolism ( Gille et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid bacteria are involved in the fermentation process in some KMC ecotypes (Chakravorty et al, 2016;Coton et al, 2017). The most beneficial genera detected in KMC samples were Bacteroides and Prevotella, which are known as dominant human gut microbiota members (Lavefve et al, 2021). Metagenomics studies also predicted opportunistic bacteria like Bacillus, Pseudomonas, etc.…”
Section: Kombucha Per Se: Echoes Of the Past Or Back To The Future Kombucha As A Multimicrobial Communitymentioning
confidence: 99%
“…Cellulose is useful for digestion because it stimulates the work of intestines that increases stool bulk and water absorption, and, thereby, decreases the gastrointestinal transit time. Earlier, we proposed KMC as a source of prebiotic for astronauts (Kozyrovska et al, 2012), and most recently, kombucha fermentation was reported to produce SCFAs (Utoiu et al, 2018;Annunziata et al, 2020) or support a significant potential prebiotic effect (Lavefve et al, 2021). The AAB, producing cellulose, are food-grade (Alexandraki et al, 2013) or GRAS bacteria (Gorgieva and Trček, 2019), which gives Komagataeibacter species potential for pro/pre/postbiotic use.…”
Section: Kombucha Dietary and Prophylaxis Projects During Spaceflightsmentioning
confidence: 99%